Analisis Usaha Dan Inovasi Produk Pada UMKM Ayam Geprek Bakar Studi Kasus Cabang Binong Jati - Permana, Devani Aprilia; Apriadi, Deri (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Ayam Geprek Bakar is a family-run culinary MSME operating in Bandung since 2020. It introduces innovation in its food processing by using a torch-burning technique for grilled smashed chicken and serving it with citrus leaf sambal, which has successfully attracted local consumers despite relying solely on word-of-mouth marketing. This study aims to analyze the product innovation strategies and marketing challenges faced by the business. A qualitative case study approach was employed, involving in-depth interviews with the business owner. The findings indicate that the uniqueness of the product serves as a key competitive advantage. However, limited digital marketing knowledge presents a challenge in expanding market reach. It is recommended that the MSME begin utilizing digital platforms to improve visibility and competitiveness in a broader market.